Penerapan Pemasaran Digital dan Penguatan Identitas Visual Sebagai Upaya Peningkatan Daya Saing UMKM Kelapa Jaya di Desa Kedungbungkus - Jaka Subrata; Candra Agustian; Dede Janaloka (JURPIKAT, 2026)
This community service activity aims to increase the capacity of Kelapa Jaya MSMEs through the application of digital marketing strategies, strengthening visual identity, and fulfilling business legality. Partner problems include limited use of digital media for promotion, unoptimized business identity, and unfulfilled legal requirements. The implementation method was carried out through observation, identification, planning, implementation, and evaluation stages. The program implementation includes creating logos, banners, managing websites and social media, registering on Google Maps, implementing QRIS, and registering a Business Identification Number (NIB). The results show that business actors are now more skilled in using digital technology for marketing. Partners also have a structured visual identity, an efficient payment system, and legal certainty through NIB. This activity has successfully increased the visibility and competitiveness of Kelapa Jaya MSMEs sustainably.